Rye production under acid soils and drought conditions: an alternative for the sustainability of high Andean livestock farming in Peru - Carrasco Chilón, William Leoncio (2023)
The rye (Secale cereale L.) crop shows a high potential to contribute to the sustainability of high Andean livestock because it supports the agroclimatic conditions and acid soils in the Peruvian Andes. The production of green forage, hay, and grain from the rye crop in acid soils was studied with the use of different levels of phosphorus and potassium fertilization in four local rye ecotypes (CBI-001, CSM-001, CJS-001, and CCE-001). The green forage yield (GFY) ranged from 32.35 to 53.62 t ha−1, dry matter from 6.05 to 8.56 t ha−1, and hay from 7.0 to 10.36 t ha−1; nutritional levels ranged from 9.02% to 13.56% protein and 6.50% to 7.75% ash levels, mainly with differences between ecotypes (p < 0.05). No differences existed between fertilization levels for the number of stems per plant, spikes per plant, and grains per ear (p > 0.05). Also, CBI-001 and CCE-001 were superior with 1868.4 and 1797.8 kg ha−1 of grain, respectively (p = 0.0072); the use of 60 kg ha of nitrogen, 120 kg ha−1 of P2O5, and 80 kg ha−1 of K2O gave higher grain and residue yields. The high nutritional value and yield of the rye ecotypes studied in acid soil conditions and without irrigation can be an alternative for livestock feeding and grain production in the rainy season in the Andes as a dual-purpose crop.